2003
DOI: 10.1007/s00280-003-0681-1
|View full text |Cite
|
Sign up to set email alerts
|

Dihydropyrimidine dehydrogenase (DPD) rapidly regenerates after inactivation by eniluracil (GW776C85) in primary and metastatic colorectal cancer

Abstract: These results demonstrate that oral administration of eniluracil inactivated DPD below the level of detection in normal tissues as well as in primary and metastatic CRC. After discontinuation of eniluracil, DPD rapidly returned toward baseline within 6 days in PBMC, normal intestinal mucosa and normal liver.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…Previous pharmacokinetic studies from our laboratory in a profoundly DPD-deficient patient demonstrated reduced 5-FU catabolism with prolonged elimination half-life compared with the "normal" population (26). Additional studies by our laboratory using eniluracil (a potent DPD inhibitor) showed similar results (27). Taken collectively, these data suggested that the reduced catabolism of 2-13 C-uracil in DPD-deficient individuals should result in a subsequent decline in 13 CO 2 levels in breath.…”
Section: Discussionsupporting
confidence: 63%
“…Previous pharmacokinetic studies from our laboratory in a profoundly DPD-deficient patient demonstrated reduced 5-FU catabolism with prolonged elimination half-life compared with the "normal" population (26). Additional studies by our laboratory using eniluracil (a potent DPD inhibitor) showed similar results (27). Taken collectively, these data suggested that the reduced catabolism of 2-13 C-uracil in DPD-deficient individuals should result in a subsequent decline in 13 CO 2 levels in breath.…”
Section: Discussionsupporting
confidence: 63%
“…Efficient inactivation of DPD by oral administration of eniluracil has been observed in primary and metastatic colorectal cancer. 341 However, eniluracil is currently withdrawn from further development because several studies showed that the combination of oral eniluracil and 5FU had lower activity compared to intravenous 5FU/LV treatment. 342…”
Section: A 5-fluorouracil (5-fu)mentioning
confidence: 99%
“…Because new DPD appears shortly after eniluracil has been eliminated, 15,16 it is important to administer an adequate dose of eniluracil that will also inactivate any DPD synthesized during the entire exposure to 5-FU. If variable amounts of DPD remain active, the regimen's highly predictable 5-FU pharmacokinetics and safety will be compromised.…”
Section: The Remedymentioning
confidence: 99%